Evaluation of Transport Properties in Warm Dense Matter Generated by Pulsed-power Discharge for Nuclear Fusion Systems. (May 2015) - Sasaki, Toru; Takahashi, Takuya; Ohuchi, Takumi; Kawaguchi, Yoshimasa; Takahashi, Kazumasa; Kikuchi, Takashi; Aso, Tsukasa; Harada, Nob.; Horioka, Kazuhiko; Nagatomo, Hideo; Fujioka, Shinsuke
Abstract: To achieve the thermonuclear fusion systems, the physical properties of warm dense matter (WDM) are key parameters. In this paper, we review the evaluation of physical properties in WDM by using pulsed-power discharges. To evaluate the thermal conductivity for a divertor wall in magnetic confinement fusion, we investigate a semi-empirical evaluation based on the experimental values for electrical resistivity. The results indicate that, in the region between the interme- diate degeneracy and the non-degeneracy, the evaluated thermal conductivity has an inflection point. To evaluate the electrical resistivity for the fuel target in the inertial confinement fusion, an isochoric heating by using pulsed-power discharge in the pressure vessel has been demonstrated. The results indicate that the electrical resistivity in WDM for gold is 100 μΩ m at 0.1ρ s (ρ s : solid density) of density and the internal energy is 1MJ / kg.